(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Accounting information systems are responsible for providing information that constitutes raw material for decision making in terms of investment, payments to suppliers, payroll, income, among others. The analysis of such information becomes a cornerstone in the positioning strategies through productivity and competitiveness of any organization. When this analysis is applied to large volumes of information, there are Big Data tools that facilitate the grouping of data according to its source or nature. This paper will describe the most influential accounting information systems in the analysis of large volumes of data that affect the decision making of companies in different sectors of the economy during the period between 2015 and 2020.